Convenient pH-responsive removal of Acid Black 1 by green l-histidine/iron oxide magnetic nanoadsorbent from water: performance and mechanistic studies. Issue 6 (23rd January 2019) - Qurrat-ul-Ain,; Khatoon, Jaweria; Shah, Muhammad Raza; Malik, Muhammad Imran; Khan, Iffat Abdul Tawab; Khurshid, Sumaira; Naz, Raheela
Abstract : Effective and eco-friendly separation of Acid Black 1 dye from water by electrostatic adsorption onto reusable Histidine-Fe3 O4 nanoparticles, credited to their pH-responsiveness. Abstract : This study was aimed at developing green histidine-modified Fe3 O4 nanoparticles (His-MNPs) for the adsorptive removal of Acid Black 1 (AB1) from aqueous solution. The His-MNPs were characterized by atomic force microscopy, scanning electron microscopy-energy dispersive X-ray spectrometry, infra-red spectra and thermogravimetry. These MNPs were spherical (average diameter 11–28 nm) with polydispersity index of 1.40 and about 13% mass coating of histidine. To optimize AB1 adsorption on His-MNPs and understand its mechanism, the influences of different operational variables (pH, adsorbent amount, temperature, initial AB1 concentration, contact time, ionic strength, etc. ) on adsorption were examined with adsorption isotherms, kinetics and thermodynamic studies. The AB1 adsorption from water was fast with equilibrium time ≤ 45 min. The adsorption equilibrium was best fitted to the Langmuir isotherm model ( q max = 166.7 mg g −1 at the adsorbent dose of 0.2 g L −1, temperature 30 °C and pH 4). The linearity order for other isotherms was as follows: Dubinin–Radushkevich (D–R) < Temkin < Freundlich. The kinetics of the AB1 adsorption demonstrated the best compliance with the pseudo-second-order model, predominantly controlled by film diffusion as compared to intraparticle diffusion. Thermodynamic parameters (Δ H ° and Δ G °) reflected the exothermic and spontaneous adsorption process. The values of Δ G °, Δ H °, activation energy and D–R free adsorption energy were all consistent with the physisorptive removal of AB1. The spectral (electronic and IR) and pH studies further corroborated the mechanism of AB1 removal by His-MNPs. The His-MNPs showed efficient adsorption, easy regeneration and excellent reusability, assisted by their pH-responsive properties. The prepared adsorbent can provide a safe, effective and economical alternative strategy for removing azo dyes from wastewater.